2013
DOI: 10.1002/anie.201307212
|View full text |Cite
|
Sign up to set email alerts
|

Very Strong Organosuperbases Formed by Combining Imidazole and Guanidine Bases: Synthesis, Structure, and Basicity

Abstract: New structural motives for organosuperbases, that are easy to prepare and highly basic are urgently required in many areas of chemistry. The synthesis of N,N'-bis(imidazolyl)guanidine bases (BIG bases) is reported. Their pKα  values are determined as 26.1-29.3 in THF. They are thus probably the strongest known phosphorous-free organic bases both in solution and in the gas phase. Calculations help to determine the structural and electronic factors giving rise to the high basicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…The GB values of all considered conformers for compounds 1-3 are compared in Table 2. The modelled 3Et-c2 and 3Pr-c1 guanidines, with their GB values above 1155 kJ mol −1 belong to the most basic neutral non-phosphorus all-guanidine bases and their gas-phase basicity is comparable to recently published bis-imidazolydene guanidine derivatives 20 and aforementioned bis-TBD. 7 Together with the analogues bearing 4-dimethylaminopyridine 21 or TMG subunit, achieved.…”
Section: Gas-phase Basicitysupporting
confidence: 61%
“…The GB values of all considered conformers for compounds 1-3 are compared in Table 2. The modelled 3Et-c2 and 3Pr-c1 guanidines, with their GB values above 1155 kJ mol −1 belong to the most basic neutral non-phosphorus all-guanidine bases and their gas-phase basicity is comparable to recently published bis-imidazolydene guanidine derivatives 20 and aforementioned bis-TBD. 7 Together with the analogues bearing 4-dimethylaminopyridine 21 or TMG subunit, achieved.…”
Section: Gas-phase Basicitysupporting
confidence: 61%
“…Interestingly,the tBu-N = P n (dma) system has the best fit (RMSD = 0.1) of all the investigated systems, and one of the lowest k values.T he excellent fit indirectly supports the high quality of the MeCN pK a values,w hich is remarkable,since the pK a values of the higher members of the series have been obtained by extrapolation from data in THF. Possible examples can be seen for example in the recently reported BIG bases [11] and cyclopropenimine bases. [5] Thep roposed quantitative model for predicting basicity increase resulting from expanding the molecular framework demonstrates that the GB region around 350 kcal mol À1 and beyond is well reachable with non-chelating organosuperbases.Since high-molecular-weight bases are inconvenient in practical use (owing to the large amount of base required), the real challenge in superbase design lies not in the highest possible basicity at any cost but rather in finding structural units that are both efficient in increasing basicity and being smaller.…”
mentioning
confidence: 98%
“…[4,5] Design and synthesis of new superbases has been aflourishing field of research during the last decades. [1,4] Numerous families of superbases (such as phosphazenes, [3] phosphatranes, [6] bisphosphazene proton sponges, [7,8] imidazolidines, [9] imidazolidino-phosphazenes [10] and -guanidines, [11] bis-guanidines [12] )h ave been created and potentially superbasic compound families have been proposed, for example carbenes. [13] More recently different innovative bases have been proposed, such as cyclopropeneimines [14] and silylene bases.…”
mentioning
confidence: 99%
“…[6] Yang recently showed that proazaphosphatranes (also knowna sV erkade'ss uperbases) [7] have comparable TEP values to P(tBu) 3 (Figure 1). [8] Amongt he varioust ypes of nonionic superbases, [9] proazaphosphatranes are unique because they become protonated at the phosphorus atom. [7] Hence, they were not only used as ligands in transition-metal-catalyzed transformations, [10] but more importantly found broad applications as stoichiometricb ases and as catalysts in organic synthesis.…”
mentioning
confidence: 99%